Analysis of a Curved Multi-Layer Radome Using a Flat Model and the Ray Tracing Technique - Shin, Hokeun; Yoon, Daeyeong; Choi, Kwangsik; Jung, Inkyun; Park, Yong Bae (Journal of Electrical Engineering and Technology, 2020)
An analysis method for a curved multi-layer radome using a flat model and the ray tracing technique is presented. Radiation of a curved multi-layer radome-enclosed antenna is calculated using the ray tracing technique and the reflection and transmission coefficients of a flat multi-layer radome with the same structure as the curved radome. The computed results are compared with the commercial EM simulator to validate the accuracy of our method. The radiation characteristics from the waveguide slot array antenna enclosed by the curved multi-layer radome are computed in terms of the radome shape, the dielectric constant, and the number of layers to check the efficiency of the proposed method.
Keywords: Analysis method; Number of layers; Radiation characteristics; Ray-tracing technique; Reflection and transmission coefficients; Waveguide slot array antennas; Curved multi-layer radome; Ray tracing technique; Waveguide slot array antenna